An interim evaluation of Penang’s first bike-share scheme - Nadhrah A Kadir; Lim, Ghee-Thean; Law, Chee Hong (Penerbit Universiti Kebangsaan Malaysia, 2019)
Bike-sharing schemes are gaining worldwide momentum as a non-motorized transport. The reasons why cities have jumped on the bandwagon of implementing a bike-share system are to reduce traffic congestion, to improve air quality and as an alternative transport option to move around cities. As part of the effort to be “cleaner, greener, healthier and safer,” Penang Island has decided to launch the first bike-share scheme in Penang, making it the first state in Malaysia to ever implement a bike-sharing program with a docking station. While the existing literature on bike-sharing focuses on European and North American cities, less attention is given to experiences in South East Asia, especially small cities in the South East Asia. This paper aims to fill that gap by evaluating the performance of the pioneer of the bike-sharing program in Penang; i.e. the LinkBike. Using the inaugural data from LinkBike’s first annual report, as well as data from personal interviews and grey literature, this paper attempts to understand the performance, opportunities and challenges facing LinkBike in its first year of operation. Essentially, results show that LinkBike was performing quite well considering it was the bike-share pioneer in Penang. This paper also highlights several opportunities such as attractive brands and effective outreach strategy and challenges in terms of payment method, safety concerns and lack of cycling culture. Understanding these motivators and constraints will better shape the performances of LinkBike in terms of ridership and cultivating the cycling culture in Penang.